The Influence of Amino Acids and Trace Elements on L-lysine Production by Bacillus subtilis Using Agricultural Products as Carbon and Nitrogen Sources - J. Okpalla; I. A. Ekwealor (Archives of Current Research International, 2023)
The influence of amino acids and trace elements on L-lysine production by Bacillus subtilis using agricultural products as carbon and nitrogen sources was studied. The L-lysine producing bacteria had already been isolated from Nigerian soil. They were purified and identified as Bacillus subtilis PR13 and B. subtilis PR9, using cultural, biochemical and molecular characteristics. Optimization of some parameters which included amino acids and trace elements on L-lysine production by Bacillus species was carried out. The L-lysine was produced in 100 ml flasks containing fermentation media (FM1 and FM2). The findings revealed that, enhanced lysine yield of 2.88mg/ml and 1.68 mg/ml by Bacillus subtilis PR13 and Bacillus subtilis PR9, was observed at in the presence of 0.1% (w/v) of glycine and leucine respectively. There was a negative correlation between amino acid and lysine production by the B. subtilis PR 13 (r= -0.74) and PR 9 (-0.55). The supplementation of 0.005 g/l of MgSO4.7H2O and FeSO4.7H2O enhanced optimum L-lysine yield of 2.56 mg/ml for B. subtilis PR 13 and 1.36 mg/ml for B. subtilis PR9. There was a positive correlation between MgSO4.7H2O and lysine production by the B. subtilis PR 13 (r=0.96) and FeSO4.7H2O and lysine production by B. subtilis PR9 (r= 0.94). The results obtained in the study, illustrated that the optimization of process parameters could increase L-lysine yield from agricultural products by B. subtilis PR13 and B. subtilis PR9.